KARAKTERISASI FRAKSI AKTIF ANTIBAKTERI EKSTRAK DARI DAUN PEPE (Gymnema reticulatum Br) - Swantara, I M. Dira; Darmayasa, I. B.; lestari, Sri (Jurnal Kimia (Journal of Chemistry); Vol. 4, No. 2 Juli 2010)
Isolation and caracterisation of antibacterial compounds in the leaves pepe have been carried out. Extraction was carried out by macerating using methanol and 70%. Separation of extracts which have activity to Eschericia coli and Stathylococcus aereus was conducted using the solvent partition by petroleum ether, chloroform, and ethyl acetate. The most active extract, the ethyl acetate extract was separated by column chromatography using a mixture eluent of chloroform, and ethyl acetate with a ratio of 1:1. The eluents were tested for their bioactivity as antibacterial agent and the results established that fraction 1 was the most active fraction. This next wing fraction 1 was then identified using GC-MS. The gas chromatogram showed 3 peaks at 18.658 minutes (33.69%), 19.617 minutes (34.01%), and 25.492 minutes (32.69%). It was suggested that the fraction contains three compounds. The first peak has a molecularion at m/z 296 with a base peak of 68, matches with the spectra of 3,7,11,15-tetramethyl 2-hexadesene-1-ol. The second peak, m/z 270 and 74, matches with the spectra of metyl hexadecanoate ester. The last peak has amoleculer ion at 390 and base peak at 149, suggesting it is dioctyl-1,2-benzenedicarboxylilate.
Keywords: Isolasion, caracterisation, Eschericia coly, Stathylococcus aereus, Gymnema reticulatum Br